2016
DOI: 10.3747/co.23.2830
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Sputum for the Detection of Early and Locally Advanced Non-Small-Cell Lung Cancer: A Prospective Case–Control Study

Abstract: Background Non-small-cell lung cancer (nsclc) is associated with very poor overall survival because 70% of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…In this period, 12 studies were excluded because they are reviews or meta-analyses (n=5), insu ciency information (n=3), detecting miRNA methylation (n=2) or data overlapping (n=2). As a result, 16 articles 11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] were eligible for nal meta-anlaysis. Figure 1A showed the process of studies identi cation.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this period, 12 studies were excluded because they are reviews or meta-analyses (n=5), insu ciency information (n=3), detecting miRNA methylation (n=2) or data overlapping (n=2). As a result, 16 articles 11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] were eligible for nal meta-anlaysis. Figure 1A showed the process of studies identi cation.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…These studies published from 2010 to 2018, and the sample size ranged from 30 to 315. Two studies conducted in Asian 24,27 , seven studies conducted in Caucasian 13,20,25,[28][29][30][31] and the remaining seven studies 11,19,[21][22][23]26,32 conducted in mixed population. Two studies 19,26 selected healthy population as controls, 11 studies 13,20-23,25,28-32 selected cancer-free subjects as controls, and the remaining three studies 11,24,27 applied benign pulmonary disease (BPD) as controls.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have shown that downregulations of miR‐486‐5p contribute to the development of NSCLC by regulating Pim‐1 and ARHGAP5 . We and others have also demonstrated that aberrant miRNA expressions detected in sputum biologically reflect those in primary lung cancer . We have recently developed a panel of two sputum miRNA (miR‐31‐5p and miR‐210‐3p) biomarkers for NSCLC with 65% sensitivity and 89% specificity .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] We and others have also demonstrated that aberrant miRNA expressions detected in sputum biologically reflect those in primary lung cancer. [9][10][11][12][13][14][15] We have recently developed a panel of two sputum miRNA (miR-31-5p and miR-210-3p) biomarkers for NSCLC with 65% sensitivity and 89% specificity. 16 Furthermore, efforts have been made to develop cell-free (eg, plasma) biomarkers by detecting the circulating molecules directly released from lung tumors.…”
Section: Introductionmentioning
confidence: 99%